EMPIRICAL MODELS OF THE RELATIONSHIP BETWEEN RELIGION AND STATE IN INDONESIA: HOW RELIGIOUS BELIEFS DEFINE THE RELATION BETWEEN RELIGION AND STATE? - Handi Hadiwitanto; Carl Sterkens (LIPI Press, 2015)
In Indonesian political context the plausibility of religion is very high, both at individual and at societal level. People normally think that religion and state are not seen as totally independent. Religion should not be marginalised in public policies, and the state should deal with religious matters. In the same time we found the rise of religious fundamentalism and its influence on Indonesian politics. This particular situation shows the problematic relationship between religion and state in Indonesia. The dividing line between religion and state in today’s Indonesia is very thin at some points; and the role of religion in the legislative and executive branch receives a lot of attention in public debate. In this article we would like to examine empirically the attitudes of Indonesian students in higher education towards the relationship between religion and state. We will elaborate on the relationship between the religious convictions of individuals, and the influence of these convictions on their ideas about the separation of religion and state. We expect that university students attitudes are highly relevant regarding respect for religious freedom in domains where the state exercises control. The tension between religion and state is indeed visible in concrete legislation. Keywords: religion-state relation, liberalism, communitarianism, religion, Islam, Kristen, empirical research, Indonesia